Optimizing nitrogen fertilization in maize: the impact of nitrification inhibitors, phosphorus application, and microbial interactions on enhancing nutrient efficiency and crop performance - Malakshahi Kurdestani, Ali; Francioli, Davide; Ruser, Reiner; Piccolo, Alessandro; Maywald, Niels Julian; Chen, Xinping; Müller, Torsten (Frontiers in Plant Science, 2024)
Despite the essential role of nitrogen fertilizers in achieving high crop yields, current application practices often exhibit low efficiency. Optimizing nitrogen (N) fertilization in agriculture is, therefore, critical for enhancing crop productivity while ensuring sustainable food production. This study investigates the effects of nitrification inhibitors (Nis) such as Dimethyl Pyrazole Phosphate (DMPP) and Dimethyl Pyrazole Fulvic Acid (DMPFA), plant growth-promoting bacteria inoculation, and phosphorus (P) application on the soil-plantmicrobe system in maize. DMPFA is an organic nitrification inhibitor that combines DMP and fulvic acid for the benefits of both compounds as a chelator. A comprehensive rhizobox experiment was conducted, employing varying levels of P, inoculant types, and Nis, to analyze the influence of these factors on various soil properties, maize fitness, and phenotypic traits, including root architecture and exudate profile. Additionally, the experiment examined the effects of treatments on the bacterial and fungal communities within the rhizosphere and maize roots. Our results showed that the use of Nis improved plant nutrition and biomass. For example, the use of DMPFA as a nitrification inhibitor significantly improved phosphorus use efficiency by up to 29%, increased P content to 37%, and raised P concentration in the shoot by 26%, compared to traditional ammonium treatments. The microbial communities inhabiting maize rhizosphere and roots were also highly influenced by the different treatments. Among them, the N treatment was the major driver in shaping bacterial and fungal communities in both plant compartments. Notably, Nis reduced significantly the abundance of bacterial groups involved in the nitrification process. Moreover, we observed that each experimental treatment employed in this investigation could select, promote, or reduce specific groups of beneficial or detrimental soil microorganisms. Overall, our results highlight the intricate interplay between soil amendments, microbial communities, and plant nutrient dynamics, suggesting that Nis, particularly DMPFA, could be pivotal in bolstering agricultural sustainability by optimizing nutrient utilization.